DESAIN INTERIOR PADA COFFEE SHOP KOPI TOKO DJAWA BANDUNG DARI MASA KE MASA - Laila Destyantari (Jurnal PATRA, 2022)
Kopi Toko Djawa is a coffee shop building that was originally a historic bookstore called Djawa Bookstore located in Bandung. Toko Buku Djawa itself was built in 1955 with an owner named Mrs. Tjoe who is from Central Java. Active as a bookstore for 60 years, Toko Buku Djawa finally officially closed and stopped operating in 2015. At the end of 2017, precisely in December, Toko Buku Djawa officially transformed into a coffee shop that is now known as Kopi Toko Djawa. This research will examine how the interior design journey applied to this coffee shop over time. Using qualitative methods and descriptive analysis in this study, data collection is carried out by jumping directly into the field and also equipped with secondary data in the form of scientific journals, photos, and websites. The step now taken by the owner of Kopi Toko Djawa is to use the existing building with new functions but still maintain the atmosphere of the 1950s and traditional interiors that already exist. For some elements of space fillers such as shelves and storefronts where books are displayed are still presented so that the impression that has been left by Toko Buku Djawa before is not lost. Kopi Toko Djawa located at Jalan Braga no. 81 Bandung can be one of the inspirations in building a coffee shop with a simple and traditional interior theme and concept.